Origin of the anomalous electromechanical interaction between a moving magnetic dipole and a closed superconducting loop. (1st April 2022) - Zhang, Hongye; Yang, Tianhui; Li, Wenxin; Xin, Ying; Li, Chao; Iacchetti, Matteo F; Smith, Alexander C; Mueller, Markus
Abstract: Lenz's law states that 'the current induced in a circuit due to a change in a magnetic field is directed to oppose the change in flux and to exert a mechanical force which opposes the motion'. This statement has been widely adopted to predict many effects in electromagnetism. However, multiple recent experimental measurements have shown that the interactions between a moving permanent magnet (PM) and a closed superconducting loop can disobey the fundamental statement of Lenz's law: during the entire process of a PM threading a high temperature superconducting (HTS) coil, the current induced in the HTS coil keeps the same direction, and thus the mechanical force exerted on the PM does not always oppose its movement. The seeming 'Lenz's law-violated phenomenon', namely the anomalous electromechanical interaction between a moving PM and a closed superconducting loop, can bring about numerous potential applications in the domains of superconducting magnetic energy storage, electromagnetic ejection, and flux pumps, etc. However, the cause of this anomalous phenomenon remains controversial. By representing the PM as a magnetic dipole, taking the perfect conductor approximation for the closed superconducting loop, this paper has theoretically studied the anomalous electromechanical effect with rigorous mathematical formulae derivation. The proposed analytical equations have been verified by numerical modelling and experimental measurements, which further confirms the effectiveness of the perfect conductor approximation in ease of calculation. Results have shown that both the induced electromotive force and the intrinsic properties of the conductive loop (resistance-dominant or inductance-dominant) determine together the electromechanical performance of the studied energy conversion system, and the nearly zero resistivity of superconductors is the dominant cause of the anomalous phenomenon. This paper has illuminated the origin of the anomalous electromechanical interaction between a moving magnetic dipole and a closed superconducting loop, provided an efficient and reliable tool to predict the electromechanical performance of the studied energy conversion system, and is believed to deepen people's understanding of the interactions between magnetic field sources and superconductors.